Internet connectivity disruption in Ukraine (Ukraine) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ukraine. Data sourced from IODA.
Network Disruption Incident ID: UA-2026-0059. Severity: critical. Confidence: 67%